Effects of Oral Multi-Vitamin Multi-Mineral Supplement Formulations on Laboratory Outcomes and Quality of Life: A Quasi-Experimental Study - Jittat, Nawin; Pongpirul, Krit; Tepwituksakit, Bhakanij; Iammaleerat, Pratchayada; Heath, Julia; Lungchukiet, Palita; Taechakraichana, Nimit; Charukitpipat, Artirat (Frontiers in Nutrition, 2022)
Background Multi-vitamin multi-mineral (MVMM) products often come in several single-substance capsules from different manufacturers. Attempts to mix several vitamins and minerals into one MVMM product have been complicated and often involve legal concerns. This study aimed to comparatively investigate the changes in laboratory parameters and quality of life (QOL) among individuals who received different MVMM formulations. Methods This three-arm non-randomized controlled trial was conducted at VitalLife Scientific Wellness Center (VSWC), Bangkok, Thailand. A total of 72 healthy adult individuals with total serum 25-(OH)D level of 20-29 ng/ml were invited to choose from the three available options: (1) Hydro-Cell-Key (HCK®, Hepart AG, Switzerland) contains Vitamin D3 2,000IU, Vitamin C 1,000mg, Vitamin E 166mg, Vitamin A 1mg, Coenzyme Q10 30mg, natural Carotenoids 8mg, and citrus flavonoids 200mg in granule formulation; (2) VTL-7 (VWSC) contains similar vitamins and mineral but in capsule formulation; and (3) placebo capsule (no supplement). The 36-Item Short-Form Health Survey (SF-36) was used to measure serum micronutrients and QOL at baseline, month 3, and month 6. A generalized estimating equation (GEE) was used to compare the repeated-measure outcomes across the three groups. This study was registered at the Thai Clinical Trial Registration (TCTR20190205002) and approved by the Bumrungrad International Institutional Review Board (BI-IRB No.258-10-18PhFub). Results Both VTL-7 and HCK saw a significantly higher increase in Vitamin D than placebo at month 3 and 6—VTL-7 from 25.15±2.13 to 35.53±6.11 (p<0.001) and 33.38±6.89 (p<0.001); HCK from 24.25±3.08 to 28.43±5.93(p=0.005) and 27.40±5.24(p=0.012); placebo from 24.00±2.73 to 23.05±4.39(p=0.273) and 22.30±6.23(p=0.200), respectively. Likewise, β-carotenoids of VTL-7 vs HCK groups significantly increased from 0.88±0.68 vs 0.94±0.55 at baseline to 3.03±1.79(p<0.001) vs 1.09±0.61(p=0.125) and 3.26±1.74(p<0.001) vs 1.15±0.66(p=0.064), respectively. These findings were corroborated through the GEE analysis. Other micronutrients at month 3 and month 6 did not increase significantly from baseline in any group. The overall QOL among the three groups in terms of physical (p=0.560) and mental (p=0.750) increased but werewas not statistically significant. Conclusion MVMM supplements in capsule formulation increased serum levels of some micronutrients to a higher extent than that of granule formulation. Participant adherence remains a potential confounder and should be further explored.